Prevalence of Recurrent Aphthous Stomatitis in University Students and Its Relation with Anxiety - Atena Shiva; Jamshid Yazdani Charati; Azim Elkaei; Maryam Zamanzadeh (Journal of Mazandaran University of Medical Sciences, 2019)
Background and purpose: Recurrent aphthous stomatitis (RAS) or oral aphthous are among the most common problems in adults. Stressful events could cause these ulcers. The purpose of this study was to determine the prevalence of recurrent aphthous stomatitis among students in Mazandaran University of Medical Sciences and its relationship with anxiety. Materials and methods: In this analytical cross-sectional study, 683 students in Mazandaran University of Medical Sciences (2018) were selected via random classification. Data were collected using Cattle Anxiety Scale and RAS history form. Data analysis was done in SPSS V22 applying descriptive and analytical tests. Results: The prevalence of RAS in this study was 21.8%. A significant relationship was found between the history of RAS and anxiety level in students (P= 0.04). Conclusion: Students investigated showed different degrees of anxiety that affected the rate of RAS. Therefore, appropriate planning and strategies are needed to control anxiety and subsequent problems such as RAS.